Are 25 SNPs from the CARDIoGRAM study associated with ischaemic stroke?. Issue 9 (30th April 2013) - Lövkvist, H.; Sjögren, M.; Höglund, P.; Engström, G.; Jern, C.; Olsson, S.; Smith, J. G.; Hedblad, B.; Andsberg, G.; Delavaran, H.; Jood, K.; Kristoffersson, U.; et al.
Abstract : Background and purpose: The Coronary Artery Disease Genome‐Wide Replication and Meta‐Analysis Study (CARDIoGRAM) reported 25 single‐nucleotide polymorphisms (SNPs) on 15 chromosomes to be associated with coronary artery disease (CAD) risk. Because common vascular risk factors are shared between CAD and ischaemic stroke (IS), these SNPs may also be related to IS overall or one or more of its pathogenetic subtypes. Methods: We performed a candidate gene study comprising 3986 patients with IS and 2459 control subjects. The 25 CAD‐associated SNPs reported by CARDIoGRAM were examined by allelic association analysis including logistic regression. Weighted and unweighted genetic risk scores (GRSs) were also compiled and likewise analysed against IS. We furthermore considered the IS main subtypes large‐vessel disease (LVD), small‐vessel disease and cardioembolic stroke [according to Trial of Org 10172 in Acute Stroke Treatment (TOAST)] separately. Results: SNP rs4977574 on chromosome 9p21.3 was associated with overall IS [odds ratio (OR) = 1.12; 95% confidence interval (CI): 1.04–1.20; P  = 0.002] as well as LVD (OR = 1.36; 95% CI: 1.13–1.64; P  = 0.001). No other SNP was significantly associated with IS or any of its main subtypes. Analogously, the GRSs did not show any noticeable effect. Conclusions: Besides the previously reported association with SNPs on chromosome 9p21, this study did not detect any significant association between IS and CAD‐susceptible genetic variants. Also, GRSs compiled from these variants did not predict IS or any pathogenetic IS subtype, despite a total sample size of 6445 participants.